2020
DOI: 10.1029/2019jb018383
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Quantitative Tensile Testing of Antigorite in a Transmission Electron Microscope

Abstract: The determination of the mechanical properties of serpentinites is essential toward the understanding of the mechanics of faulting and subduction. Here we present the first in situ tensile tests on antigorite in a transmission electron microscope. A push‐to‐pull deformation device is used to perform quantitative tensile tests, during which force and displacement are measured, while the evolving microstructure is imaged with the microscope. The experiments have been performed at room temperature on 2 × 1 × 0.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…(2020) and Idrissi et al. (2020) showed a total lack of dislocation activity in antigorite, where strain occurs only by shear cracks and cataclasis at grain boundaries, which are observed in our samples (e.g., Figure 7). The development of CPOs was proposed to occur through the formation and progressive rotation of antigorite blades by sliding along the basal plane (i.e., the [001] plane; Hansen et al., 2020); a similar mechanism has also been considered responsible for the formation of CPOs in calcite deformed in the brittle regime (Demurtas et al., 2019).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…(2020) and Idrissi et al. (2020) showed a total lack of dislocation activity in antigorite, where strain occurs only by shear cracks and cataclasis at grain boundaries, which are observed in our samples (e.g., Figure 7). The development of CPOs was proposed to occur through the formation and progressive rotation of antigorite blades by sliding along the basal plane (i.e., the [001] plane; Hansen et al., 2020); a similar mechanism has also been considered responsible for the formation of CPOs in calcite deformed in the brittle regime (Demurtas et al., 2019).…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, it is unlikely that antigorite has five independent slip systems (i.e., the Von Mises criterion cannot be met). The two most recent studies (Hansen et al, 2020;Idrissi et al, 2020) actually show that the dislocations observed in antigorite may not even truly contribute to deformation. These facts suggest that completely plastic flow of antigorite cannot be achieved in the deformation of antigorite.…”
mentioning
confidence: 99%
“…Transmission electron microscopy investigations of naturally and experimentally deformed samples highlight kink bands which have orientations consistent with slip along both a and b directions of intact sheets (Auzende et al., 2015, Figures 4e and 4f). However, during tensile in‐situ transmission electron microscopy experiments (Idrissi et al., 2020), movement of dislocations was not observed ‐ as it was for other materials deformed using the same technique (Idrissi et al., 2016); instead evidence for grain boundary sliding parallel to grain cleavage is observed.…”
Section: Discussionmentioning
confidence: 96%
“…The systematic variation of our data during individual tests and consistency with the LTP flow law suggest that the creep rate is limited by the same underlying plastic mechanism over the explored range of conditions. For layered materials like antigorite, previous work shows that deformation is accommodated by basal shear mechanisms, which can involve sliding along shear microcracks or grain boundaries (e.g., “asperity friction” Escartin et al., 1997; Hansen et al., 2020; David et al., 2020; Idrissi et al., 2020), basal and sub‐basal dislocations (e.g., (001), (101), and (10true1 $\overline{1}$) systems (Amiguet et al., 2014; Auzende et al., 2015)), or ripplocations (Gruber et al., 2016). The mechanical basis for the LTP law suggests that moving defects along these crystallographic planes encounter a “barrier” which can be overcome by stress or thermal activation.…”
Section: Discussionmentioning
confidence: 99%
“…In the uniaxial tension test [41][42][43][44][45][46], which is schematically illustrated in Fig. 1.2 b, deformation and failure of the thin film specimen occur under uniform stress acting along a single axis.…”
Section: Strength and Toughness Testing Of Thin Filmsmentioning
confidence: 99%